Designing A Better User Experience: User Centered Design Methods For Digital Art Collection Portals - Rika Ratri Anggraeni; Budhi Kristianto (SISFORMA, 2024)
The use of digital art collection portals and platforms has been growing rapidly in the digital era. However, many users face access and navigation challenges due to the complicated interface and inefficient search system. Therefore, this research aims to optimize the user experience on digital art collection portals by applying the user-centered design (UCD) method which focuses on web-based user interfaces (UI/UX). Calculations of the System Usability Scale (SUS) are used to quantify a system usability. This study focuses specifically on the millennial generation, the primary users of digital art, and identifies the unique challenges they face. By presenting a user-centered design (UCD) based solution, this research makes an important contribution to the understanding of user-centered design (UCD) optimization in the context of digital arts and culture. UI/UX testing shows that the system's usability and user experience have improved significantly. By integrating these insights, digital art collection portals can better meet users' needs and expectations, improve accessibility, and increase appreciation of digital art.